An improved flamelet/progress variable modeling for supersonic combustion. (19th January 2021) - Shan, Fanli; Zhang, Dingrui; Hou, Lingyun; Fang, Hong; Zhang, He; Zhang, Jun
Abstract: In order to dynamically describe the transition of the scalar dissipation rate of the mixture fraction variance from near-wall regions to mainstream in near-wall combustion, the traditional flamelet/progress variable (FPV) model, which can be used either within the Reynolds Averaged Navier Stokes (RANS) framework or the large-eddy simulation (LES) framework, is modified to form an improved FPV model within the framework of the improved delayed detached eddy simulation (IDDES). The model blends respective expressions of the scalar dissipation rate within the RANS and LES frameworks into a unified form with an employment of the IDDES concept. It also adopts an analogy between the mixture fraction variance and turbulent kinetic energy. A hydrogen-fueled near-wall combustion is simulated to validate this model. Large-scale turbulent structures, which can either locally enhance combustion or cause local extinction in the reacting zone, are reproduced. Due to the blockage to lateral extents of spanwise turbulent structures, a three-dimensional effect, that the low temperature fluid at lower corners of flow passage is forced to move away from sidewalls, is also reproduced. The results show that the improved FPV model can avoid the scalar over-mixing effect of the traditional FPV model by delaying and mitigating the development of the mixture fraction variance at the near-wall regions. Therefore, the starting point of the high temperature zone predicted by the improved FPV model is downstream of that predicted by the traditional FPV model. It is indicated that the improved FPV model tends to delay combustion. This tendency is also demonstrated by the less combustion efficiency in the upstream region predicted by the improved FPV model. As a result, it can generate a moderate growth of the mixing and reacting zone in the longitudinal direction, which therefore improves the predictions of the species concentrations. In contrast, the traditional FPV model thickens the mixing and reacting zone, which is negative to the combustion efficiency in the downstream region. It is implied that a reasonable development of the mixture fraction variance at near-wall regions is essentially required for near-wall combustion simulation using the FPV model within the IDDES framework. Highlights: An improved FPV model for near-wall combustion is originally proposed. It describes transition of scalar dissipation rate by incorporating IDDES concept. It gives better predictions in species concentrations than traditional FPV model. It avoids over-mixing effect comparing with traditional FPV model.